AN UNUSUAL CASE OF PRIMARY FALLOPIAN TUBE CANCER - Rozhkovska, Natalia; Sumtsov, Dmytro; Sumtsov, Heorhii; Smiyan, Svitlana; Savenko, Tetiana; Gladchuk, Ihor (Eastern Ukrainian Medical Journal, 2025)
Introduction. Cases with an open ampullary opening among primary fallopian tube cancer (PFTC) are extremely rare, highly malignant, and difficult to diagnose. Primary fallopian tube cancer accounts for 1.8% of female genital cancers and about 4-6% of cancers of the uterine appendages. According to available data, the incidence of this tumour has increased up to 4 times in recent decades. Preoperative diagnosis of the PFTC has been and remains an unresolved problem for cervical cancer, which leads to untimely treatment or treatment in non-oncological institutions. Even during surgeries, errors reach 50%, which provokes inadequate surgeries and treatment methods and delays the recovery of patients. Objective: to demonstrate a case of misdiagnosis during surgery, the need for oncological care and a detailed study of the macro preparation in the operating room. Material and Methods: the results of clinical, morphological and immunohistochemical examination of the case of primary fallopian tube tract and analysis of publications in the relevant literature. Results and Discussion: The clinical, morphological and immunohistochemical analysis of an unusual case of primary fallopian tube cancer was performed. The diagnosis was made only after a routine histological and immunohistochemical examination. A broader review of this clinical case will improve cancer screening and diagnosis. Primary fallopian tube cancer remains a rare but challenging problem in terms of diagnosis and treatment. Improving diagnostic accuracy is based on a thorough preoperative examination of patients with any pathological changes in the uterine appendages, including the study of tumour markers of epithelial tumours (CA-125, НE-4, etc.). In recent years, the prevention of cancer of the fallopian tubes, ovaries, pelvic peritoneum and mammary glands by opportunistic salpingectomy has been actively implemented, with cases of primary and metastatic tumours in the fallopian tubes being reported. There have been some reports of malignant tumours developing after ‘preventive’ surgeries, although the cause of such outcomes is unknown, and the question of whether they can be avoided remains open. Conclusion: Only cancer awareness and careful examination of the removed material in the operating room and the use of suboperative morphological diagnostics will allow avoiding such errors during surgery. Abnormal uterine bleeding cannot be the result of a tumour microsite.